Pilihan Karir Lulusan Program Studi Akuntansi Keuangan di Politeknik Pos Indonesia - SATRIA, MUHAMMAD RIZAL (JURNAL RISET AKUNTANSI JAMBI, 2019)
Challenge in the accounting profession has competitively increased since the implementation of the ASEAN Economic Community (AEC) by 2015. The Indonesian accounting graduates should be ready to face a very tight competition with other graduates from outside Indonesia. Therefore, the strategy needs to be prepared, to help graduates determine selections carrier they will take. The carrier selections for graduates are the very beginning stage of career establishment. Economics-Accounting Graduates will be facing different selections of accountant profession, such as government accountants, accountants educators, company accountants, and public accountant. Or even accounting graduates can also have a career outside the accounting field if they are talented and expertise enough in another field. There are many studies related to career selections of accounting graduates has been made, but this kind of research has not been done in Financial Accounting Studies Program at the Politeknik Pos Indonesia. This research was quantitative with a descriptive cross-sectional design. The study was conducted in October 2016 using a questionnaire with a sample as many as 51 graduates using a whole sampling technique. The results showed that the majority of graduate accounting courses at the Politeknik Pos Indonesia in 2016 were female (70.59%) and the most demanding professions are Public accountants (37.25%). The location is the most demanding jobs are in Indonesia (36.47%). Selection work sector showed no significant differences between the public sector (45.09%) and private (47.05%).